2017
DOI: 10.4171/rlm/754
|View full text |Cite
|
Sign up to set email alerts
|

Optimal bounds for periodic mixtures of nearest-neighbour ferromagnetic interactions

Abstract: We provide a general framework for the optimal design of surface energies on networks. We prove sharp bounds for the homogenization of discrete systems describing mixtures of ferromagnetic interactions by constructing optimal microgeometries, and we prove a localization principle which allows to reduce to the periodic setting in the general nonperiodic case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…With this identification the energy becomes a simple nearest-neighbour interaction energy in dimension two, of which we can compute the Γ-limit in the surface scaling. Reinterpreting the limit in dimension one gives the form (11) after some technical arguments. The interest in this example is that the limit is characterized by the non-trivial topology of the graph of the connections i, j with c ε ij = 1, which is the same as that of nearest-neighbours in dimension two.…”
Section: Figure 1: Optimal Configurations For Different Volume Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this identification the energy becomes a simple nearest-neighbour interaction energy in dimension two, of which we can compute the Γ-limit in the surface scaling. Reinterpreting the limit in dimension one gives the form (11) after some technical arguments. The interest in this example is that the limit is characterized by the non-trivial topology of the graph of the connections i, j with c ε ij = 1, which is the same as that of nearest-neighbours in dimension two.…”
Section: Figure 1: Optimal Configurations For Different Volume Fractionsmentioning
confidence: 99%
“…In all those cases the limit problem is of the form (4). Applications of this result comprise the description of quasicrystalline structures [8,14] and optimal design problems for networks [11,12]. Moreover, the homogenization result for periodic systems has been recently extended to some types of antiferromagnetic interactions when the limit is instead parameterized on partitions into sets of finite perimeter [9] and can be written as a sum of energies of the form (4).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, example 2.8 shows that for infinite range interactions this is in general not true. In [15,16] it is shown that, as the periodicity T of the interactions tends to +∞, it is possible to approximate any norm as surface energy density satisfying suitable growth conditions. We refer to [2] for a random setting where it is shown that an isotropic energy density (and thus non-crystalline) can be obtained in the limit.…”
Section: Introductionmentioning
confidence: 99%
“…In that case we are mixing two types of connections in a cubic lattice. A simplified description of the two-dimensional setting for nearest neighbour-interactions can be found in [17]. The first step in the homogenization method is to consider all possible ϕ in the periodicbond setting; that is, when i → c i,ξ are periodic, in which case ϕ is independent of x.…”
Section: Introductionmentioning
confidence: 99%